Carrier accumulation in the active region and its impact on the device performance of InGaN-based light-emitting diodes. (16th November 2017) - Han, Dong-Pyo; Shim, Jong-In; Shin, Dong-Soo
Abstract: Carrier recombination and transport processes play key roles in determining optoelectronic performance characteristics such as the efficiency droop and forward voltage in InGaN/GaN multiple-quantum-well (MQW) light-emitting diodes (LEDs). In this work, we investigate the dominant carrier transport and recombination processes inside and outside the MQW region as functions of injection current from the viewpoint of carrier-energy-loss mechanisms. It is experimentally shown that carrier accumulation and subsequent spill-over at MQW active layers due to the insufficient carrier recombination rate, mainly the radiative recombination rate, explain the dependences of both the efficiency droop and the forward voltage on the injection current.